The Effect of Risk-Based Capital and Claim Ratio on the Financial Performance of Insurance Companies - Nur Azizah; Rida Perwita Sari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The insurance industry has developed rapidly enough to cause intense competition between companies. In competition, it is necessary to have good work prospects and public trust, one of which is having a healthy financial performance. Financial performance can be influenced by several factors, namely risk-based capital and claim ratio. The study analyzed whether risk-based capital and claim ratios affect financial performance. The population of this study is insurance companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. This research uses quantitative methods with purposive sampling methods with a total sample of 15 companies over 5 5-year period. The data used in this study are secondary data obtained through the company’s financial statements and annual reports. The results of this study indicate that risk-based capital affects financial performance. Meanwhile, the claim ratio does not affect financial performance.